Novel immunoassay and rapid immunoaffinity chromatography method for the detection and selective extraction of naringin in Citrus aurantium. Issue 7 (14th March 2016) - Qu, Huihua; Zhang, Yue; Qu, Baoping; Cheng, Jinjun; Liu, Shuchen; Feng, Shenglan; Wang, Qingguo; Zhao, Yan
Abstract : In this work, a novel monoclonal antibody specific for naringin was prepared and characterized. Subsequently, an indirect competitive enzyme‐linked immunosorbent assay for naringin was developed, with an effective range from 4.8 to 156 ng/mL naringin. Next, an immunoaffinity column was obtained by coupling anti‐naringin monoclonal antibodies to CNBr‐activated Sepharose 4B and a rapid immunoaffinity chromatography assay for naringin was developed. The immunoaffinity column was used to separate naringin from Citrus aurantium . The results showed that 1 g of the dry Sepharose 4B can couple 10 mg of immunoglobulin G. And the immunoaffinity column can efficiently and specifically capture approximately 250 μg of naringin without cross reacting with its structurally similar compounds. Moreover, our results indicate that the application of immunoaffinity chromatography can simplify the pretreatment and the isolation process greatly compared to conventional methods, providing a potential method for extracting the target component from structurally similar compounds in natural products.